An action research approach to supporting elite student-athletes in higher education - McKenna, J.; Dunstan-Lewis, N. (European Physical Education Review, 2004)
Support for elite student-athletes was explored within a single English university using Stringer`s (1996) Look, Think, Act model of action research. Entry to the ongoing support programme is competitive and participation is voluntary, with sessions delivered every second week after lectures. Based on supporting documentation, interviews, focus groups and participation in a long-standing voluntary support programme, we developed a perspective on the daily life of university elite student-athletes. According to their achievements, these student-athlete participants were `elite` in both academic and sporting terms. Tutors, heads of department, administrators and managers of sports services within the university contributed supplementary interviews. Based on a systematic thematic analysis of contributions, which was subsequently verified by student-athletes, three main areas of concern were identified: (1) establishing priorities of the `student`and `athlete`roles, (2) relationships with academia and (3) lack of support and understanding. The programme has been altered to reflect these issues. Further discussion focuses on unresolved issues and continuing development.